What image of the U.S.A is carried out by the brand levi's in Europe? The perspective of the portuguese consumers - Ferreira, Ana Catarina Fonseca (2020)
Thisthesis investigatesthe U.S.A.image carried out by Levi’s in the perspective of Portuguese consumers.A mixed approach was followed, composed by30 in-depth semi-structured interviewsand a quantitative design with 136 valid responses.The insightssuggest that theimageconveyed by Levi’s is static,dependsonage andgroupinteractionsand is based on three mainelements: brand history,brand personalityand association toother American brands.The Brand Image dynamism shows tonot affect U.S.A. image, whichisaligned withLevi’s Identity. However, the gap between thecurrent Brand Image andIdentity might not beneficiate the brand.